The elastic moduli across various types of resin/dentin interfaces - Pong Pongprueksa (2018)
Objective: The purpose of this study was to evaluate the elastic moduli of an unfilled adhesive resin (Adper™ Single Bond) and a filled adhesive resin (Adper™ Single Bond 2) used with and without a low-viscosity resin (LVR) (Filtek™ Flow) as an elastic cavity wall in class V composite restorations, restored with a hybrid resin composite (Z250). Methods: Buccal class V cavities were prepared on extracted premolars and lined with (1) the unfilled adhesive resin, (2) the filled adhesive resin, (3) the unfilled adhesive resin and the flowable composite, and (4) the filled adhesive resin and the flowable composite. All cavities were restored with the hybrid resin composite. The specimens were cut bucco-lingually, embedded in epoxy resin and polished. The polished specimens were evaluated for the elastic modulus with nano-indentation test at the layer of dentin, hybrid layer, adhesive resin, low-viscosity resin and resin composite. Results: The elastic moduli were 25,111 MPa for dentin, 12,243 MPa for hybrid layer of Adper™ Single Bond, 11,765 MPa for hybrid layer of Adper™ Single Bond 2, 7595 MPa for Adper™ Single Bond, 8430 MPa for Adper™ Single Bond 2, 13,543 MPa for Filtek™ Flow and 24,494 MPa for Filtek™ Z250 resin composite. The statistical analysis demonstrated that the elastic moduli were significantly different among layers (p < 0.05) except between hybrid layers of unfilled and filled adhesives (p = 1.0). Conclusion: The application of filled adhesive did not increase the elastic modulus of hybrid layer when compared with the unfilled adhesive resin. The modulus of filled adhesive resin was significantly higher than that of unfilled adhesive resin. © 2008 Academy of Dental Materials.